Clinical Correlates of Deliberate Self-Harm Among Migrant Trauma-Affected Subgroups - Baralla, Francesca; Ventura, Martina; Negay, Nikolay; Di Napoli, Anteo; Petrelli, Alessio; Mirisola, Concetta; Sarchiapone, Marco (Frontiers in Psychiatry, 2021)
Introduction: Studies have shown that exposure to a potentially traumatic events (PTEs) during the migration process has serious consequences for mental health. Migrants with a history of PTEs are more likely to inflict deliberate self-harm (DSH), a spectrum of behavior that includes non-suicidal self-injury (NSSI). With reference to a nonclinical sample of trauma-exposed migrants, this study aims to explore the prevalence of DSH, and to assess the association with socio-demographic characteristics and clinical conditions, with particular attention to post-traumatic stress disorder symptoms (PTSD), resilience capabilities, and feelings of hopelessness. Methods: A sample of migrants who had undergone a baseline evaluation at an outpatient department of the National Institute for Health, Migration and Poverty (INMP). Migrants with a history of torture, rape or other severe forms of psychological, physical or sexual violence, were invited to undergo screening at the Institute’s Mental Health Unit. Trauma-exposed migrants completed a series of self-report questionnaires which assessed the presence of PTSD, depression, anxiety, suicidal ideation, resilience and feelings of hopelessness, in addition to DSH. Univariate and multivariate log-binomial regression models were used to test the association of age and clinical characteristic of migrants with DSH. Prevalence ratio (PR) with 95% confidence intervals (95%CI) and p-values were estimated. Results: 169 migrants (76.9% males), aged between 18 and 68 years (M = 28.93; DS = 8.77) was selected. The 26.6% of the sample were frequently engaging in some form of DSH and 30.2% were diagnosed with at least one trauma related disorder DSH behaviors were most common in single and unemployed migrants as well as in subjects with posttraumatic stress symptoms, feelings of anxiety, hopelessness, low capability of resilience and suicidal ideation. Taking into account age and hopelessness, we found that PTSD and low resilience capabilities were associated with a higher risk of DSH (PRadj:2.21;95%CI(1.30-3.75) and PRadj:2.32;95%CI(1.16-4.62), respectively). Conclusion: Given the association between trauma-exposure and DSH among migrants, exploring the presence of DSH behavior within the immigrant community is crucial for the implementation of measures to develop intervention in a clinical setting.